A study of water consumption in two Malaysian Resorts - Tang, Fu Ee (World Academy of Science, 2012)
In the effort to reduce water consumption for resorts, more water conservation practices need to be implemented. Hence water audits need to be performed to obtain a baseline of water consumption, before planning water conservation practices. In this study, a water audit framework specifically for resorts was created, and the audit was performed on two resorts: Resort A in Langkawi, Malaysia; and Resort B in Miri, Malaysia. From the audit, the total daily water consumption for Resorts A and B were estimated to be 180 m³ and 330 m³ respectively, while the actual water consumption (based on water meter readings) were 175 m³ and 325 m³. This suggests that the audit framework is reasonably accurate and may be used to account for most of the water consumption sources in a resort. The daily water consumption per guest is about 500 litres. The water consumption of both resorts is poorly rated compared with established benchmarks. Water conservation measures were suggested for both resorts.